match each expression in the first column with its value in the second column in the figure below
We have to match the expression in the first column with its value in the second column.
We will use BODMAS rule to simplify the expression.
(a).
$\begin{array}{rcl}\left(6+2\right)\xb7\left(5+3\right)& =& \left(8\right)\xb7\left(8\right)\\ & =& 8\xb78\\ & =& 64\end{array}$
Therefore, $\left(6+2\right)\xb7\left(5+3\right)=64$
(b).
$\begin{array}{rcl}\left(6+2\right)\xb75+3& =& \left(8\right)\xb75+3\\ & =& 8\xb75+3\\ & =& 40+3\\ & =& 43\end{array}$
Therefore, $\left(6+2\right)\xb75+3=43$
(c).
$\begin{array}{rcl}6+2\xb75+3& =& 6+10+3\\ & =& 19\end{array}$
Therefore, $\begin{array}{rcl}6+2\xb75+3& =& 19\end{array}$
(d).
$\begin{array}{rcl}6+2\xb7\left(5+3\right)& =& 6+2\xb7\left(8\right)\\ & =& 6+2\xb78\\ & =& 6+16\\ & =& 22\end{array}$
Therefore, $6+2\xb7\left(5+3\right)=22$.